A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Chindwin basin of Manipur, India - Shangningam, Bungdon; Vishwanath, Waikhom (Zootaxa, 2013)
Psilorhynchus chakpiensis, new species, is described from the Chakpi River, Chindwin basin in Manipur, India. It is distinguished from its congeners by a combination of characters: a dome-shaped rostral cap with horizontally arranged pointed tubercles, 1–2 rows of prominent globular papillae behind the upper lip, three unbranched and nine branched dorsal-fin rays, 30–31 lateral-line scales, head width 74–83% HL, and characteristic colour bands on the dorsal and caudal fins. It is distinguished from all congeners in having a caudal-fin pattern consisting of two black bars, one incomplete bar near the base of the upper lobe, and a complete bar across the centre of the fin, traversing from the upper to the lower margin of the fin.